GENE ACTION AND HETEROSIS FOR YIELD AND YIELD COMPONENTS IN SUMMER SQUASH (cucurbita pepo L.) USING HALF DIALLEL CROSSES. - Zhiyan A. T.; Mohammed A. Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to determine some genetic parameters of summer squash (cucurbita pepo L.), half diallel cross among eight inbred lines carried out in summer season 2021 at field of College of Agricultural Engineering Sciences, University of Duhok. The experiment lay out using randomized complete block design with three replications. The results revealed that the mean square for all genotypes was highly significant effect in all studied traits. The inbred lines LBL2 and CNS2881 was superior in yield plant-1 obtained 9.67 kg and 10.94 kg, the crosses (CNS2881 x PEP1670) and (PEP1670 x N33133) recorded the highest value 13.83 and 13.53 respectively. The crosses (PEP512 x, CNS2881), (CNS2881 x PEP1670) and (PEP1670 x N33133) revealed significant heterosis for most traits. The heritability in broad sense was higher than narrow sense heritability in all traits ranged between 0.949 and 0.827 for fruit diameter and fruit weight. The average degree of dominance was higher than one in all traits except fruit length and fruit diameter.